Impact of Technical Analysis and Corporate Social Responsibility on Banking Firm Value (Jurnal Manajemen Bisnis, 2026)
This study aimed to examine the influence of technical analysis and corporate social responsibility (CSR) on the firm value of PT. Bank Rakyat Indonesia (Persero) Tbk. A quantitative approach was employed, utilizing a survey method with questionnaires distributed to the employee population. The sampling technique was saturated sampling, and the data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The measurement model evaluation confirmed the reliability and validity of the constructs, while the structural model demonstrated a satisfactory fit and substantial explanatory power. The results revealed that both technical analysis and corporate social responsibility had a positive but statistically insignificant effect on firm value at the standard significance level. However, the structural model explained a high degree of variance, indicating that these variables collectively provide a strong framework for firm value. These findings suggest that while individual strategies may not directly drive firm value independently, their collective presence provides a robust framework for market perception. The implication is that companies should focus on a strategic synergy between technical market approaches and CSR programs to build sustainable corporate value.